Utilization of Instructional Resources for Effective Implementation of Life Skills Education in Secondary Schools in Kenya - Magutah , Abysolom Kuria; Nyabisi , Emily; Beth , Mwelu Mutilu (African Journal of Education,Science and Technology (AJEST), 2018)
The teaching of life skills education was introduced in Kenyan schools in 2008, so as to equip learners with the adaptive abilities for effective living. The purpose of this study was to investigate the use of instructional resources for the effective implementation of life skills education in public secondary schools in Kenya. The research objectives were: to investigate the availability of the instructional resources; to investigate the frequency of utilization of the instructional resources; and to investigate the effect of utilization of the instructional resources on the implementation of life skills education. The study adopted a concurrent triangulation research design, and data was collected using questionnaires and interview schedules. The sample size of 123 teachers and 16 principals was determined using simple random sampling and purposive sampling respectively. The data was analyzed using descriptive statistics and thematic analysis. The findings of the study showed that the availability and level of utilization of instructional resources for the implementation of life skills education was still low; and this compromises the effective implementation of life skills education. The study recommends that all public secondary schools be provided with adequate instructional resources for implementation of life skills education; and that teacher educators emphasize the need for utilizing instructional resources for effective implementation of life skills education.